UPAYA GURU SEKOLAH DASAR NON KEPENDIDIKAN DALAM MENGEMBANGKAN KOMPETENSI PEDAGOGIK - Rosyid, Ainur; Marwan, Rudi Heri (Eduscience : Jurnal Ilmu Pendidikan, 2018)
AbstractThis study aims to describe in depth on non-educational elementary school teacher effort in developing the pedagogical competence. As for the intended pedagogical competence includes knowledge about the characteristics of learners, mastering learning theory and principles of learning, curriculum development, instructional activities to educate, develop the potential of students, communication / interaction with students, and assessment and evaluation. The method used is a method of research using a qualitative approach. The data collection techniques used were interviews, and documentation. This study is expected to be a guide or reference for non-educational teachers in developing pedagogical competence. For principals, this study can be used as a reference or basis for making policy in developing non-educational pedagogical competence of teachers. Keywords: development, teacher non-educational, pedagogical AbstrakPenelitian ini bertujuan untuk menguraikan secara mendalam mengenai upaya guru SD non kependidikan dalam mengembangkan kompetensi pedagogiknya. Adapun kompetensi pedagogik yang dimaksudkan meliputi menguasai karakteristik peserta didik, menguasai teori belajar dan prinsip-prinsip pembelajaran, pengembangan kurikulum, kegiatan pembelajaran yang mendidik, pengembangan potensi peserta didik, komunikasi/interaksi dengan peserta didik, dan penilaian dan evaluasi. Metode penelitian yang digunakan adalah metode penelitian dengan menggunakan pendekatan kualitatif. Adapun teknik pengumpulan data yang digunakan adalah wawancara, dan dokumentasi. Penelitian ini diharapkan dapat menjadi panduan atau referensi bagi guru non kependidikan dalam mengembangkan kompetensi pedagogik. Bagi kepala sekolah, penelitian ini dapat dijadikan acuan atau dasar untuk mengambil kebijakan dalam mengembangkan kompetensi pedagogik guru non kependidikan. Kata kunci: pengembangan, guru non kependidikan, kompetensi pedagogik